1991
DOI: 10.19182/remvt.9176
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilité <em>in vitro</em> et dégradabilité in situ dans le rumen de ligneux fourragers disponibles sur pâturages naturels au Sénégal. Premiers résultats

Abstract: Pour évaluer l'utilisation digestive des ligneux fourragers disponibles sur pâturages naturels des zones soudanienne et sahélienne du Sénégal, leur digestibilité in vitro (méthode de Tilley-Terry) et leur dégradabilité dans le rumen (méthode in situ) sont déterminées. Sur 58 échantillons analysés in vitro, la digestibilité in vitro de la matière sèche est en moyenne de 51 avec des extrêmes de 88 à 26 %. La digestibilité in vitro de la matière organique a varié de 84 à 15 avec une moyenne de 42 %. Trente-huit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The crude protein (CP) content of the treated rice straw increased as urea-molasses treatment increased from 0 to 4% such increase may be traced to the addition of urea (non-protein nitrogen) (Ramirez et al, 2007). Earlier studies (Fall, 1988;Aregheore, 2005) observed increase in crude protein content (6-15%) of corn stover treated with 0% and 7% fertilizer grade urea. Whereas, Golmahi et al (2006) obtained a small increment (4%) in CP of barley straw treated with urea at 0 and 4%.…”
Section: Resultsmentioning
confidence: 95%
“…The crude protein (CP) content of the treated rice straw increased as urea-molasses treatment increased from 0 to 4% such increase may be traced to the addition of urea (non-protein nitrogen) (Ramirez et al, 2007). Earlier studies (Fall, 1988;Aregheore, 2005) observed increase in crude protein content (6-15%) of corn stover treated with 0% and 7% fertilizer grade urea. Whereas, Golmahi et al (2006) obtained a small increment (4%) in CP of barley straw treated with urea at 0 and 4%.…”
Section: Resultsmentioning
confidence: 95%
“…Os CDMS e CDFDN para a silagem exclusiva de FS foram de 71,23 e 62,78 %, respectivamente. Estes resultados foram ligeiramente inferiores aos encontrados por Vaz et al (1998), avaliando a inclusão de feno de flor de seda ao feno de Coast-cross, que verificaram para a FDN 66,34 % de digestibilidade, e semelhantes ao de Fall (1991) que, avaliando a digestibilidade in vitro das folhas de flor de seda, encontrou valor de 72 % para a MS.…”
Section: Discussionunclassified
“…A C. procera vem sendo explorada na região Semi-árida como forrageira, seja através da fenação natural, seja com a pré-secagem pós trituração. Esta planta possui 20,97% de matéria seca, ENN de 34,80 % e teor de proteína variando de 13,61 % (OLIVEIRA, 2002) a 19,42 % (ABBAS, 1992) e, quando na forma de feno, seu teor protéico se eleva para 21,23 % (VAZ et al, 1998), com digestibilidade da matéria seca e matéria orgânica, apenas das folhas, de 72 e 68 %, respectivamente (FALL, 1991), além de possuir alguns princípios farmacológicos com ação abiótica (AKHTAR, 1992). Aliado aos valores nutritivos desta forrageira, observa-se que sua produção na região semi-árida ocorre durante todo o ano, apresentando seu pique de produção no período das chuvas, momento em que há excedente de forragem nesta região.…”
Section: Introductionunclassified